2020
DOI: 10.3389/fpsyt.2020.575867
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal 5-Year Follow-Up Study of Cognitive Function After First Episode Major Depressive Disorder: Exploring State, Scar and Trait Effects

Abstract: Major depression (MDD) is associated with cognitive deficits in processing speed and executive function (EF) following first episode (FE). It is unclear whether deficits are state or trait related. Studies following FE MDD over longer periods are lacking, making it uncertain how cognition and symptoms develop after the initial episode. The present study assessed cognitive function and symptoms 5 years following FE MDD. In addition, the study explored relationships between MDD symptoms, rumination, and cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 65 publications
2
17
0
Order By: Relevance
“…Wekking et al ( 53 ) also found persisting deficits in most cognitive measures, except inhibition. Both studies used a contrast score that only approached statistical significance and results similar to other studies ( 30 , 63 ).…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Wekking et al ( 53 ) also found persisting deficits in most cognitive measures, except inhibition. Both studies used a contrast score that only approached statistical significance and results similar to other studies ( 30 , 63 ).…”
Section: Resultsmentioning
confidence: 66%
“…This conclusion was supported in findings from several studies conducted by Schmid and Hammar ( 62 ), who stated that impaired inhibition on the stroop test, in addition to semantic fluency, is present early in the course of MDD, indicating that EF represents a trait in MDD, irrespective of symptom severity and number of previous episodes. Moreover, the authors showed that impairment in inhibition and switching and semantic fluency in first-episode MDD persisted in long-term follow up ( 63 ), with the former associated with relapse during the first year after the first episode ( 30 ), and with deficits in inhibition in a subgroup with relapse 5 years later ( 64 ), suggesting a relationship between impaired ability in EF of inhibition and switching and relapse in MDD. These findings were also evidenced in patients with recurrent depression and showed that impaired inhibition in the acute phase persisting in phases of symptom reduction ( 65 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Employing multivariate latent growth models across gender would be recommended to test for these differences more accurately (Gomez-Baya et al, 2017). The “Scar Hypothesis” of depression refers mainly to neurobiological changes, with “scars” being a result of prolonged depression episodes (e.g., Ronold et al, 2020). Given that this was a non-clinical study involving a non-clinical and non-stratified sample, interpretations are made with caution and generalizations are difficult to attain.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the annual and lifetime prevalence rates are as high as 6.6 and 16.2% ( 1 ). Recurrences leave patients with a heavy economic burden, a lower quality of life, and could be incremental ( 2 ). Between 50 and 90% of patients with depression complain about sleep disturbances ( 3 ).…”
Section: Introductionmentioning
confidence: 99%